Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\dfrac{1}{2}\left(\dfrac{2}{2\cdot3\cdot4}+\dfrac{2}{3\cdot4\cdot5}+...+\dfrac{2}{18\cdot19\cdot20}\right)\)
\(=\dfrac{1}{2}\left(\dfrac{1}{2\cdot3}-\dfrac{1}{3\cdot4}+\dfrac{1}{3\cdot4}-\dfrac{1}{4\cdot5}+...+\dfrac{1}{18\cdot19}-\dfrac{1}{19\cdot20}\right)\)
\(=\dfrac{1}{2}\left(\dfrac{1}{6}-\dfrac{1}{380}\right)\)
\(=\dfrac{187}{2280}\)
Ta có: \(\left(\frac{1}{1.2.3}+\frac{1}{2.3.4}+\frac{1}{3.4.5}+...+\frac{1}{8.9.10}\right)x=\frac{23}{45}\)
\(\Rightarrow\frac{1}{2}\left(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+\frac{1}{3.4}-\frac{1}{4.5}+...+\frac{1}{8.9}-\frac{1}{9.10}\right)x=\frac{23}{45}\)
\(\Rightarrow\frac{1}{2}\left(\frac{1}{1.2}-\frac{1}{9.10}\right)x=\frac{23}{45}\)
\(\Rightarrow\frac{1}{2}\left(\frac{1}{2}-\frac{1}{90}\right)x=\frac{23}{45}\)
\(\Rightarrow\frac{11}{45}x=\frac{23}{45}\)
\(\Rightarrow x=\frac{23}{45}:\frac{11}{45}\)
\(\Rightarrow x=\frac{23}{11}\)
Đặt A=\(\frac{1}{1.2.3}+\frac{1}{2.3.4}+\frac{1}{3.4.5}+...+\frac{1}{8.9.10}\)
2A=\(\frac{2}{1.2.3}+\frac{2}{2.3.4}+\frac{2}{3.4.5}+...+\frac{2}{8.9.10}\)
2A=\(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}\) \(+\frac{1}{3.4}-\frac{1}{4.5}+...+\frac{1}{8.9}-\frac{1}{9.10}\)
2A=\(\frac{1}{1.2}-\frac{1}{9.10}\)
2A=\(\frac{22}{45}\)
A=\(\frac{22}{45}\div2\)
A=\(\frac{11}{45}\)
\(\Rightarrow\frac{11}{45}.x=\frac{23}{45}\)
\(x=\frac{23}{45}\div\frac{11}{45}=\frac{23}{11}\)
Vậy x=\(\frac{23}{11}\)
\(M=1.2.3+2.3.4+3.4.5+...+47.48.49\)
\(4M=1.2.3.4+2.3.4.\left(5-1\right)+3.4.5.\left(6-2\right)+...+47.48.49.\left(50-46\right)\)
\(=1.2.3.4+2.3.4.5-1.2.3.4+3.4.5.6-2.3.4.5+...+47.48.49.50-46.47.48.49\)
\(=47.48.49.50\)
\(M=\frac{47.48.49.50}{4}=1381800\)
Tính:
S = \(\frac{1}{1.2.3}+\frac{1}{2.3.4}+\frac{1}{3.4.5}+\frac{1}{4.5.6}+...+\frac{1}{98.99.100}\)
\(2S=\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{99.100}\)
\(2S=\frac{1}{2}-\frac{1}{9900}\)
\(2S=\frac{4949}{9900}\)
\(S=\frac{4949}{19800}\)
Ta xét : \(\frac{1}{1.2}-\frac{1}{2.3}=\frac{2}{1.2.3}\)
\(\frac{1}{2.3}-\frac{1}{3.4}=\frac{2}{2.3.4}\)
...
\(\frac{1}{98.99}-\frac{1}{99.100}=\frac{2}{98.99.100}\)
Ta có : 2S = \(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{98.99}-\frac{1}{99.100}\)
=> 2S = \(\frac{1}{1.2}-\frac{1}{99.100}\)
=> 2S = \(\frac{4949}{9900}\)
=> S = \(\frac{4949}{19800}\)
A = 1/2 - 1/3 - 1/4 + 1/3 - 1/4 - 1/5 + 1/4 - 1/5 - 1/6
A = 1/2 - 1/6
A = 1/3
k mk nha. ths bn nhìu nha
A = 1/2.3 - 1/ 3.4 + 1/3.4 - 1/4.5 + 1/4.5 -1/5.6
= 1/2.3 - 1/5.6
= 1/6 - 1/30
= 2/15
Vậy A = 1/15
\(\frac{3x}{5}=\frac{1}{1.2.3}+\frac{1}{2.3.4}+...+\frac{1}{6.7.8}\)
Ta có: \(\frac{1}{1.2.3}+\frac{1}{2.3.4}+...+\frac{1}{6.7.8}\)
\(=\frac{1}{2}.\left(\frac{2}{1.2.3}+\frac{2}{2.3.4}+...+\frac{2}{6.7.8}\right)\)
\(=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{6.7}-\frac{1}{7.8}\right)\)
\(=\frac{1}{2}.\left(\frac{1}{1.2}-\frac{1}{7.8}\right)\)
\(=\frac{1}{2}.\left(\frac{1}{2}-\frac{1}{56}\right)\)
\(=\frac{1}{2}.\frac{27}{56}=\frac{27}{112}\)
\(\frac{3x}{5}=\frac{27}{112}\)
\(\Rightarrow3x=\frac{27.5}{112}\)
\(\Rightarrow3x=\frac{135}{112}\)
\(\Rightarrow x=\frac{45}{112}\)
~Học tốt~
you spammed
giúp tôi pro